The place of American Women : economic exploitation of women - Jordan, Joan (Boston: New England Free Press, 1968)
"Joan Jordan Overdruk uit Revolutionary Age, vol. 1, 3 als deel van een speciale uitgave over 'American Women and the Radical Movement'."